USABILITY EVALUATION OF EARLY DETECTION AND POSTPARTUM COMPLICATION CONSULTATION SOFTWARE BY POSTPARTUM MOTHERS - Nurhayati; Pertiwi, Mumpuni Intan; Kholilurrohman, Maulana Rifky; Tamarussal, Naraya Kyesa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The postpartum period is a phase following childbirth that is vulnerable to various health complications. This paper aims to describe postpartum mothers’ assessment of the usability of an early detection and health complication consultation software during the postpartum period. Usability evaluation was conducted using the System Usability Scale (SUS) method to efficiently assess user perceptions of the technology system in terms of satisfaction and acceptance. The paper adopts a descriptive quantitative approach, with methods including questionnaire design, data collection, SUS score processing, result interpretation, and formulation of improvement recommendations. The study results show an average SUS score of 79.67, which falls into the A- category, indicating an acceptable level of user acceptance and a rating scale classified as Good. The majority of respondents found the application useful due to its ease in selecting symptoms, speed of assessment results, and direct consultation features, although there were suggestions for further feature development and service quality enhancement